PERANCANGAN SISTEM MANAJEMEN PERUBAHAN JADWAL PERKULIAHAN DI LABORATORIUM DENGAN PENERAPAN METODE DevOps - Elvi Rahmi; Eva Yumami; Kasmawi; Wiwin Saputra (Politeknik Negeri Bengkalis, 2023)
Optimal laboratory availability holds utmost importance in the pursuit of educational and research objectives at Politeknik Negeri Bengkalis. Confronting the global challenges and competition in today's digital age, Politeknik Negeri Bengkalis finds it imperative to ensure the effective and efficient utilization of its academic resources. Through observations, it has been noted that instances of suboptimal laboratory usage are not uncommon due to instructors' absence from the laboratory as per the designated schedule. This circumstance renders the laboratories unused, consequently disrupting the teaching and learning process. The focal point of this research is to craft academic administration software at Politeknik Negeri Bengkalis, enabling the real-time monitoring of laboratory availability and seamless adjustment of laboratory usage schedules. This ambitious task is undertaken using the innovative DevOps application development methodology. The adoption of the DevOps application development approach yields significant advantages throughout the stages of development, testing, and eventual implementation of this application.